PENGARUH PENERAPAN ANGGARAN BERBASIS KINERJA, KUALITAS LAPORAN KEUANGAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA KEUANGAN BIRO UMUM SEKRETARIAT DAERAH PROVINSI KEPULAUAN BANGKA BELITUNG - Adrian Radiansyah; Rizki Auliddiah; Suhardi Suhardi (Jurnal Akuntansi dan Pajak, 2023)
This study aims to determine and analyze the effect of implementing performance-based budgeting, quality of financial reports, and clarity of budget targets on financial performance at the Secretariat General of the Regional Secretariat of the Bangka Belitung Islands Province. In this study, the independent variables are performance-based budget execution, quality of financial reports, and clarity of budget targets, and the dependent variable is financial performance. This research method uses a quantitative method with a descriptive approach which aims to find out how the influence of the implementation of performance-based budgeting, the quality of financial reports, and the clarity of budget targets on financial performance. Source of data is primary data obtained by distributing questionnaires and interviews. While other secondary data obtained from literature, journals, and others. The results of this study indicate that partially, the implementation of performance-based budgeting, the quality of financial reports, and the clarity of budget targets have a positive and significant impact on financial performance. While the results of the simultaneous test also show that the independent variables simultaneously have a positive effect on financial performance.